Fostering Teachers-Led Open Education in Universities: Recommendations Emerging from Research - Nascimbeni, Fabio; Burgos, Daniel; Tlili, Ahmed (2019 7th International Conference on ICT and Accessibility, ICTA 2019, 2021)
The paper presents some recommendations on how to foster the adoption of open education practices within universities starting from the capacities and challenges of university educators, based on the central role that educators play within the process of adopting openness within higher education. Those advices derive from the research work run within the Open Educators factory project, that has collected data from more than 1000 educators worldwide on their level of adoption of open educational practices, ad want to represent starting points for discussions on how to implement openly in a useful and cost-effective way within universities.
Keywords: higher education; OER; open education; open educational practices; teachers education; Scopus(2); WOS(2)